Aspects on the optimization of die-sinking EDM of tungsten carbide-cobalt - Amorim,Fred Lacerda (2010)
At present, due to their properties, the tungsten carbide-cobalt (WC-Co) composite materials are in huge demand by industry to manufacture special tools, dies/molds and components under erosion. The powder metallurgy is the usual process applied to obtain WC-Co products, but in some cases this process is unable to produce tools of very complex shapes and highly intricate details. Thus, additional conventional and non-conventional machining processes are required. In this context, the electrical discharge machining (EDM) is an efficient alternative process. However, the EDM parameters have to be properly set for any different tungsten carbide-cobalt composition and electrode material to achieve an appropriate level of machining performance. In this work, a special grade of tungsten carbide-cobalt was used as workpiece and a copper-tungsten alloy as electrode. Experiments on important EDM electrical and non-electrical parameter settings with reference to material removal rate, electrode wear ratio and surface roughness were carried out under typical rough and finish machining. This paper contributes with an attempt to provide insightful guidelines to optimize electrical discharge machining of WC-Co composite materials using CuW alloy electrodes.